Awareness and participation of farmers in extension activities of agricultural media resources and extension centre in Ogun State (2013)
This study assessed the extension activities of Agricultural Media Resources and Extension Centre (AMREC) of University of Agriculture Abeokuta, Ogun State. Five villages that were in active collaboration with the centre were targeted. Ten percent (10%) of registered farmers were selected from each village given the sample size of 170 respondents. Data based on respondents awareness and participation in the extension activities of AMREC were collected through structured questionnaire and analysis was done using both descriptive and inferential statistics. The study revealed that 69.6% of the respondents were between 31-50years of age, 68.3% were males, 88.8% were married and 62.7% of the respondents have one form of education or the other. Majority (82.6%) were full time farmers with 44.7% cultivating 1-2hectares while 95.0% had technical background before the inception of AMREC in the area. Greater percentage (59.0%) of the respondents had been having contacts with extension agents once in 2 weeks. All the respondents were aware of AMREC research activities but 95% had more awareness on market research. Respondents were aware of extension services of AMREC more than research activities and almost all the respondents were aware of input supply services of AMREC. Meanwhile, participation of respondents in research activities of AMREC was occasional while that of extension and input supply activities was regular. There is significant relationship between gender, marital status, level of education and level of participation in AMREC activities (χ2= 20.31, p<0.05; χ2= 6.92, p<0.05 and χ2= 21.58, p< 0.05). Positive relationship exists between respondents’ awareness of all AMREC activities and participation in the extension activities. It can be concluded that most of the participants in AMREC activities were small scale farmers and their awareness and participation in AMREC extension and input supply activities were more than research activities. More female farmers and farmers with large hectares of land should be involved. Also, AMREC should ensure that their research work is disseminated to all farmers within their coverage areas irrespective of the specific target audience.